3D Feedback control using fuzzy logic for a curvature-controllable steerable bevel-tip needle. (June 2020) - Xu, Binxiang; Ko, Seong Young
Abstract: Owing to numerous advantages to patients, percutaneous intervention has become a popular research topic in recent decades. To improve trajectory following accuracy, many robotic steering systems have been developed using various advanced control algorithms. To overcome the complicated modeling procedures, this study proposed a three-dimensional (3D) feedback control method based on fuzzy logic for a steerable needle that did not require an exhaustive mathematical derivation. A 3D kinematic model of a curvature-controllable steerable (CCS) needle was obtained, and the spatial trajectory following controller using fuzzy logic for the CCS needle was presented. A series of simulations using the kinematic model were carried out to validate the accuracy of the model and control strategies. The experimental results showed that the proposed control system could accurately steer the CCS needle along a 3D path.